2007
DOI: 10.1007/s11606-007-0244-y
|View full text |Cite
|
Sign up to set email alerts
|

Appointment-Keeping Behavior is Not Related to Medication Adherence in Hypertensive African Americans

Abstract: OBJECTIVE:The relationship between appointmentkeeping behavior, medication adherence (ADH), and systolic and diastolic blood pressure (SBP and DBP) was assessed in 153 hypertensive African Americans followed in a community-based practice.METHODS: ADH was assessed with a self-report questionnaire. BP was obtained from electronic medical records and appointment attendance was determined from the log of all appointments made during the 12-month study period. Nonadherence rates were compared across appointment att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
2
12
2
Order By: Relevance
“…The Morisky scale has been used in other studies of black patients with HTN. (35-37) In our sample, the Cronbach's alpha was 0.67, which is consistent with the estimate of Morisky et al(34)…”
Section: Methodssupporting
confidence: 92%
“…The Morisky scale has been used in other studies of black patients with HTN. (35-37) In our sample, the Cronbach's alpha was 0.67, which is consistent with the estimate of Morisky et al(34)…”
Section: Methodssupporting
confidence: 92%
“…A similar rate of 12.0 % was reported in a cross-sectional survey of 185 hypertensive African-Americans in an urban medical center in Maryland, USA [3]. However, as high as 31.0 % of hypertensive African-Americans followed in a community based practice in New York City missed more than 30.0 % of follow-up appointments [15]. Among the diabetic respondents in this study, 13.0 % missed more than 30 % of their follow-up appointments.…”
Section: Discussionsupporting
confidence: 65%
“…Findings from this study aligned with those of other investigators who suggest that appointment adherence is not an accurate substitute for medication taking behavior. For instance, in a cross-sectional study, Ogedegbe and his colleagues found no significant relationship between appointment adherence and medication adherence among 190 hypertensive African-Americans followed in a community health center in New York [15]. ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Missing physician office visits was also not associated with adherence as in another study of minority hypertensive patients. 41 Finally, elderly patients who were prescribed at least four antihypertensive medications were less adherent, as in other studies. 29 In response to an elevated blood pressure, physicians may simply add another drug instead of counselling about medication adherence.…”
Section: Discussionmentioning
confidence: 67%